Друковані засоби масової інформації Донбасу в 1923-1924 рр. - Алієва, Е. (Схід, 2012)
У статті автором зроблена спроба проаналізувати розвиток друкованих засобів масової інформації Донбасу в період нової економічної політики. Характеризується кількісний
і якісний склад друкованої періодики регіону, основні заходи центральної влади щодо
преси та особливості реалізації їх на місцях. This article attempts to detail and thoroughly analyze the development of print media Donbas during the new
economic policy, keeping the thought that the press was and remain a powerful influence weighed on the formation
of public opinion research that requires special attention of historians. The article characterized by quantitative,
qualitative composition of printed periodicals in the region, the main activities of the central government on the press
and especially the implementation of the city.